Championship Concepts For Marching Percussion - HANNUM, Thom (Hal Leonard Publishing Corp., 1986)
Chapter I: Organization and Instrumentation Chapter II: Building a Musically Viable Program Technique Chapter III: The Rehearsal Chapter IV: Orchestration Chapter V: Field and Visual Aspects.